CuO nanoparticles prepared by alcohol-assisted hydrothermal synthesis for gas-sensing application: effect of pH value - Hung, Nguyen Manh; Hoat, Phung Dinh; Hung, Pham Tien; Hoang, Nguyen Van (Communications in Physics, 2023)
CuO nanoparticles were synthesized by alcohol-assisted hydrothermal method at various pH values, using sodium hydroxide as a precursor for pH control. The chemical composition, morphological and structural properties of the obtained CuO nanoparticles were investigated by the Raman and energy-dispersive X-ray spectroscopies, the field-emission scanning electron microscopy, and the X-ray diffraction. The results reveal that although the pH value does not affect the formation of the CuO phase, it strongly influences the crystalline size, the morphology, and the particle-agglomeration level of CuO. The differences in the morphology and the crystalline size of CuO nanoparticles are ascribed to various H+/OH- ratios of the growth solution. Meanwhile, with the optimized particle size, the CuO nanoparticles-based sensor can be used as a potential candidate for CO and/or H2 detection.